Motivational Interviewing in Improving Oral Health: A Literature Review - Farghal, Malak; Mounir, Zaghez (European Dental Research and Biomaterials Journal, 2025)
Motivational interviewing (MI) is a counseling strategy approach conceptualized by William R. Miller and Stephen Rollnick. It is a collaborative conversation style which helps strengthen a person's own motivation and commitment to change. The interview is conducted to help the person explore and resolve their ambivalence, by expressing their motivations and strengthening their capacity for change. This new approach is used in almost of medical disciplines, including dentistry. This article in the theoretical part treats the different motivational theories, principles, spirit, and practice of MI in dentistry. In the practical part, the article discusses the effectiveness of MI in clinical settings, particularly for improving patient outcomes. It emphasizes the importance of tailoring MI to meet the unique needs of high-risk populations and ensuring the sustainability of MI interventions. The article also highlights the potential benefits of targeting specific groups for future research on MI, aiming to enhance its application in various health care contexts.
Keywords: motivation; periodontal disease; oral health; motivational counseling; motivational interviewing; interview; stages of changes; oral; dental